PECULIARITIES OF MANAGEMENT OF PUBLIC EDUCATIONAL INSTITUTIONS IN THE PEDAGOGICAL HERITAGE OF M. ANDRIEVSKY (Pedagogy of Higher and Secondary Education, 2011)
The article reveals the basic ideas of the famous educator, the headmaster of Gadyach secondary boerding school namea after E. P. Kochergin of Poltava Regional Council M. Andriyevskyi regarding the management features of the secondary boarding educational facilities in the context of the development of the management behaviour theory and practice in the field of education in the second half of the twentieth century.
Keywords: school organization; management behaviour; buarding school; educational process; teaching staff; full and harmonious upbringing of the individual